Profesi Pendidik dan Kode Etik Pendidikan dalam Pemikiran Abû Ishâq Al-Kannânî - Ali Mudlofir (Ulumuna, 2011)
Teachers are one of the important factors in the success of education including Islamic Education. Hence, teachers are considered as respected profession-bearing consequences of standardized characters and ethics as part of teaching competence. Teachers are not only considered as instructors but also spiritual facilitators leading to the students to be insân kâmil, integrated human being. Considering such an important role, it is not wondering that studies on profession and teaching ethics have been profoundly found. This article studies those aspects from the perspective of Abû Ishâq al-Kannânî reconstructed from his work, Tadzkirat al-Sâmi‘ wa al-Mutakallim fî Adabi al-‘Âlim wa al-Muta‘alim. The writer relates al- Kannânî’s thoughts to Indonesian contexts.